Complications in Idiopathic Pulmonary Fibrosis: Focus on Their Clinical and Radiological Features - Galioto, Federica (Diagnostics (Basel), 2020)
Idiopathic pulmonary fibrosis (IPF) is a fibrotic lung disease with uncertain origins and pathogenesis; it represents the most common interstitial lung disease (ILD), associated with a pathological pattern of usual interstitial pneumonitis (UIP). This disease has a poor prognosis, having the most lethal prognosis among ILDs. In fact, the progressive fibrosis related to IPF could lead to the development of complications, such as acute exacerbation, lung cancer, infections, pneumothorax and pulmonary hypertension. Pneumologists, radiologists and pathologists play a key role in the identification of IPF disease, and in the characterization of its complications—which unfortunately increase disease mortality and reduce overall survival. The early identification of these complications is very important, and requires an integrated approach among specialists, in order to plane the correct treatment. In some cases, the degree of severity of patients having IPF complications may require a personalized approach, based on palliative care services. Therefore, in this paper, we have focused on clinical and radiological features of the complications that occurred in our IPF patients, providing a comprehensive and accurate pictorial essay for clinicians, radiologists and surgeons involved in their management.